The Nabidae (Hemiptera: Heteroptera) of Israel and the Sinai Peninsula - Novoselsky, T.; Freidberg, A.; Dorchin, N.; Meltzer, N.; Kerzhner, I. (Zootaxa, 2014)
A long-term taxonomic and faunistic survey of the family Nabidae from Israel and the Sinai (Egypt) was conducted based primarily on material housed in the National Collection of Insects at Tel Aviv University, Israel (TAUI). A key is provided to all species and information is given for each, species including its distribution, previous records from the study area and life history details if available. Eleven species are recorded; Nabis (Nabis) pseudoferus orientarius Remane and Nabis (Halonabis) sareptanus Dohrn are new records to the fauna of the study area. Phorticus velutinus velutinus Puton is expected to occur in Israel based on its current circummediterranean distribution.